Nitrogen rate and timing implementation on durum wheat in a bed planting system - Yildirim, Mehmet; Yakut, Zeki; Akinci, Cuma; Kurt, Firat; Kizilgeci, Ferhat (Universiti Kebangsaan Malaysia, 2016)
The effects of nitrogen (N) fertilization at different growth stages were investigated on durum wheat (Triticum durum L.) grain yield and yield components (with irrigated bed planting) in Diyarbakir, Turkey. N was applied at a rate of 140 kg ha–1 and distributed to one, two and three applications at various combinations with five different growth stages (i.e. sowing, seedling growth, early tillering, stem elongation and booting). This study included 13 treatments, including the control (zero nitrogen). The N application timings (NAT) of the 50% sowing + 50% early tillering and 66% sowing + 33% early tillering treatments were most suitable for durum wheat. The results showed that NAT had significant effect on flowering time, SPAD readings of the early milky ripe stage, plant density, thousand kernel weights, grain filling duration, grain filling rate, grain N content, grain yield, harvest index and grain N yield. In summary, the highest values of parameters studied were obtained from the 50% sowing + 50% first tillering and 66% sowing + 33% early tillering treatments. N fertilization application rate and time of durum wheat genotypes should consist of applying 50-60% of the total N fertilizer at sowing and 40–50% at the early tillering stage under irrigated conditions and with bed planting.